Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/20002297.2017.1281556
|View full text |Cite
|
Sign up to set email alerts
|

Dental plaque microbial profiles of children from Khartoum, Sudan, with congenital heart defects

Abstract: Few studies have focused on the bacterial species associated with the deterioration of the dental and gingival health of children with congenital heart defects (CHD). The aims of this study were (1) to examine the dental plaque of children with CHD in order to quantify bacterial load and altered bacterial composition compared with children without CHD; and (2) to investigate the correlation between the level of caries and gingivitis and dental biofilm bacteria among those children. In this cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…With regard to the oral health of the children with CHD, studies have also shown that they are more prone to prevalent and long-lasting gingival inflammation compared to their healthy counterparts (Nosrati et al, 2013;Steelman et al, 2000) and that they harbour higher counts of several bacterial species that are known to be involved in initiation and progression of caries and gingival inflammation (Steelman et al, 2000;Steelman, Rosen, Nelson, & Kenamond, 2003). We recently demonstrated that a group of Sudanese children with CHD were found to harbour altered bacterial profiles which were correlated with higher cariogenicity and perio-pathogenicity (Ali et al, 2017). However, the mechanism behind the severe and prolonged gingivitis particularly among children with CHD is still unclear.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…With regard to the oral health of the children with CHD, studies have also shown that they are more prone to prevalent and long-lasting gingival inflammation compared to their healthy counterparts (Nosrati et al, 2013;Steelman et al, 2000) and that they harbour higher counts of several bacterial species that are known to be involved in initiation and progression of caries and gingival inflammation (Steelman et al, 2000;Steelman, Rosen, Nelson, & Kenamond, 2003). We recently demonstrated that a group of Sudanese children with CHD were found to harbour altered bacterial profiles which were correlated with higher cariogenicity and perio-pathogenicity (Ali et al, 2017). However, the mechanism behind the severe and prolonged gingivitis particularly among children with CHD is still unclear.…”
mentioning
confidence: 87%
“…The amount of the bacterial members of the red complex (Tannerella forsythia (T. forsythia) , Porphyromonas gingivalis (P. gingivalis), Eubacterium nodatum (E. nodatum) and Terponema denticola (T. denticola) has previously been reported in pooled plaque samples taken from the four posterior teeth of each child in the two groups and described in detail (Ali et al, 2017). Briefly, the collected plaque samples were kept in sterile tubes and stored at −80°C.…”
Section: Plaque Bacterial Composition (Members Of the Red And Orange Complexes)mentioning
confidence: 99%
“…Among 21 studies in low- and middle-income countries, four were conducted in China, 43 46 four in India, 47 – 50 three in Brazil, 51 53 two in Saudi Arabia 54 , 55 , and one each in Argentina, 56 Bosnia Herzegovina, 57 Iran, 58 Ethiopia, 59 Guatemala, 60 and Sudan 61 . One multicentre study involving 17 low- to middle-income countries included India, Pakistan, Colombia, Russia, China, Dominican Republic, Brazil, Argentina, El Salvador, Ukraine, Peru, Mexico, Belarus, Vietnam, Uganda, Guatemala, and Bangladesh 62 …”
Section: Epidemiology Of Perioperative Infections In Low- and Middle-mentioning
confidence: 99%
“…There were five different study designs including one randomised controlled trial, 53 one non-randomised interventional before–after study, 62 16 cohort studies, 43 45 , 47 – 50 , 52 , 54 57 , 59 , 60 , 63 one case-control study, 51 and three cross-sectional studies 46 58 , 61 Most studies were conducted in children, with two in neonates 47 , 57 and two involving children and adult patients 43 50 …”
Section: Epidemiology Of Perioperative Infections In Low- and Middle-mentioning
confidence: 99%
See 1 more Smart Citation